The Relationship between Quality of E-Government and Level of Public Accountability: An Empirical Analysis of Cities/ Regencies in East Java Province - Ronny Prabowo; Angelia Taniasari (Jurnal Akuntansi dan Bisnis, 2007)
The notion that e-government supports public accountability has been widely recognized. However, empirical research on the relationship between quality of e-government and level of public accountability is still rare, even inexistent. This article aims to investigate the relationship between quality of e-government and level of public accountability. We rely on Jawa Pos 2005 score of Public Accountability to represent level of public accountability and best practice of government website in East Java Province (Probolinggo Regency) as the benchmark to measure the quality of e-government. The findings confirm popular belief that e-government and public accountability are related.